A new method to determine the causes of deviation in cylinder pressure curves of motored reciprocating piston engines. (February 2022) - Mährle, Christian; Held, Stefan; Huber, Sebastian; Wachtmeister, Georg
Simulation calibration of modern engines to test bench measurements, mainly matching the indicated pressure curves in the combustion chamber, is a time consuming task that requires high user experience to manage a multitude of adjustment parameters. In the scope of this work an automated process for calibrating simulations at motored engine operating points is presented. This is achieved using characteristic pressure deviation curves, based on 1D simulations of a simplified base model. They incorporate the dimensionless deviation of the cylinder pressure originating from one parameter. A set of these curves is scaled and superposed to recreate the original pressure deviation between simulation and measurement. The scaling factor is used to quantify each parameter's suggested adjustment value. This work presents the workflow of creating the characteristic pressure deviation curves, matching the deviation between measurement and simulation and determining the adjustment values. Further, the methodology is tested for interference of different parameters. A series of applications, ranging from 1D and 3D CFD simulation test cases to real world applications in different engines, concludes this work.